Is Platelet-rich plasma superior to whole blood in the management of chronic tennis elbow: one year randomized clinical trial - Raeissadat, Seyed Ahmad (BioMed Central, 2014)
BACKGROUND: Lateral humeral epicondylitis, or ‘tennis elbow’, is a common condition with a variety of treatment options. Platelet-rich plasma (PRP) and Autologous Whole Blood (AWB) represent new therapeutic options for chronic tendinopathies including tennis elbow. The aim of the present study was to compare the long term effects of PRP versus autologous whole blood local injection in patients with chronic tennis elbow. METHODS: Seventy six patients with chronic lateral humeral epicondylitis with duration of symptoms more than 3 months were included in this study and randomized into 2 groups. Group 1 was treated with a single injection of 2 mL of autologous leukocyte rich PRP (4.8 times of plasma) and group 2 with 2 mL of AWB. Tennis elbow strap, stretching and strengthening exercises were administered for both groups. Pain and functional improvements were assessed using visual analogue scale (VAS), Mayo score (modified Mayo Clinic performance index for the elbow) and pressure pain threshold (PPT) at 0, 4, 8 weeks and 6 and 12 months. RESULTS: All pain variables including VAS, PPT and Mayo scores improved significantly in both groups at each follow up intervals compared to baseline. No statistically significant difference was noted between groups regarding pain, functional scores and treatment success rates in all follow up examinations (P >0/05). CONCLUSION: PRP and autologous whole blood injections are both effective methods to treat chronic lateral epicondylitis and their efficacy persisted during long term follow up. PRP was not superior to AWB in long term follow up.